Caracterização do comportamento da camada limite planetaria durante a passagem de tempestades severas na região de Santa Maria, RS - Oliveira, Lucas Ilha Gandolfi de (2022)
Convective storms can significantly alter the evolution of the flow in the Planetary Boundary Layer (PBL). In this study, thermodynamic, kinematic and turbulent quantities were calculated in the PBL during the passage of convective storms by the micrometeorological tower located at the Federal University of Santa Maria (UFSM in Portuguese) in the state of Rio Grande do Sul. Ten events were subjectively selected for the study, in the day, day/night and night periods for the period from 2020 to 2022. Based on radar images, the storms were classified into discrete and multicellular, where 6 storms were discrete and 4 multicellular. For each selected event, time series of temperature (°C), pressure (hPa) and mean horizontal wind (m s-1), and relative humidity (%) were analyzed, identifying the events observing a decrease in T (cold pool), increase of p (mesohigh) and increase of Vh (gust front). The factor that most characterized the patterns of sensible heat fluxes and turbulent kinetic energy (TKE) was the degree of organization of gust fronts and cold pools. The discrete events presented better defined gust fronts and cold pools, with an increase in TKE with the arrival of the gust front and peaks of sensible heat flux maxima around the time they were recorded. After the passage of the gust front and with the establishment of the cold pool, there was cooling and intense turbulent flow (high TKE). This pattern was less defined for multicellular cases and had little dependence on the diurnal cycle. In both discrete and multicellular cases, some events showed pressure drops, some associated with heating and drying and others with cooling. Warm-up cases were associated with wake lows or mesolows. On the other hand, cases with cooling were associated with the passage of mesocyclones close to the tower. Finally, it was shown that the vertical wind shear field is drastically intensified by storms, especially discrete ones and in low layers of 5, 10, or 15 m. Such intensification is relevant, since intense vertical shallow wind shear is associated with the production of vortices in thunderstorms.